2018
DOI: 10.1186/s13054-018-2013-1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of sepsis in intensive care units in Turkey: a multicenter, point-prevalence study

Abstract: BackgroundThe prevalence and mortality of sepsis are largely unknown in Turkey, a country with high antibiotic resistance. A national, multicenter, point-prevalence study was conducted to determine the prevalence, causative microorganisms, and outcome of sepsis in intensive care units (ICUs) in Turkey.MethodsA total of 132 ICUs from 94 hospitals participated. All patients (aged > 18 years) present at the participating ICUs or admitted for any duration within a 24-h period (08:00 on January 27, 2016 to 08:00 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
67
3
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 42 publications
7
67
3
9
Order By: Relevance
“…With regard to the sepsis patients’ profile and focus of infection, Zanon et al 11 also observed a mean age of over 60 years and that the most prevalent infectious focus was the pulmonary one. Among the pathogens, Acinetobacter and Staphylococcus aureus were also frequently found, 12 being common pathogens of ventilator‐associated pneumonia (VAP). In fact, the use of mechanical ventilation in the ICU is frequent and exposes patients to the risk of developing pneumonia and consequently sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the sepsis patients’ profile and focus of infection, Zanon et al 11 also observed a mean age of over 60 years and that the most prevalent infectious focus was the pulmonary one. Among the pathogens, Acinetobacter and Staphylococcus aureus were also frequently found, 12 being common pathogens of ventilator‐associated pneumonia (VAP). In fact, the use of mechanical ventilation in the ICU is frequent and exposes patients to the risk of developing pneumonia and consequently sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of microorganisms detected, by culture type CNS, VRE, MRSAfound to be very high among patients with sepsis and septic shock in the ICU (55.7% and 70.4, respectively). The most isolated microorganism was Acinetobacter spp (33.7%) and approximately 74.8% of Acinetobacters were resistant to carbapenems(27). In our study, the rate of Acinetobacter spp in all Syrian patients was 9.3% and 23.6% in patients with sepsis.…”
mentioning
confidence: 46%
“…Ülkemizden kısa süre önce yayınlanan bir makalede, YBÜ'lerindeki enfeksiyon, sepsis ve septik şok hastalarının ancak %60'a yakınında bir etken izole edilebilmiş, küflerden sadece Aspergillus spp. raporlanmış, o da mikroorganizmaların ancak %0,3'ü olarak bildirilmiştir (12). Burada izole edilebilen etken oranının azlığına, İKE tanısı koymanın güçlüğüne ve klinik tabloların özgül olmamasına dikkat etmek gerekir.…”
Section: Epidemiyoloji: Risk Faktörleri Ve Etkenler Yönünden Genel Biunclassified